John Stuart Mill e a Filosofia das Ciências Sociais - Junta, Cristiano Moraes (Universidade Federal de São Carlos, 2011)
We analyzed John Stuart Mill s book System of Logic Inductive and Deductive. Our aim are present the philosophy of social science formulate by Mill in this book. The discussion empathize the millian interpretation of inductive methods. At last, we make the critical balance of those conceptions in relation of methodology of social science in confrontation with Emile Durkheim s opinions.
Keywords: Filosofia da ciência; Indução (Lógica); Sociologia; Philosophy of science; Induction; Sociology; CIENCIAS HUMANAS::FILOSOFIA